Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Karyawan (Studi pada Bank BSI KCP Malang Lawang) - Resti Windi Astutik; Anik Malikah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of research is examine impact on employee. data for this study are gathered through primary sources, utilizing questionnaires that are measured using a Likert scale. The respondents for employees from BSI KCP Malang Lawang. The sampling technique employed in this research involves purposive sampling, where 30 respondents are selected based on specific criteria. The data analysis is carried out using SPSS version 25. The findings of this study reveal that there is a significant positive relationship between accounting information systems and internal control systems on employee performance. Furthermore, the study indicates that Islamic economics plays a crucial role in enhancing performance in accordance with Islamic norms.Keywords: Accounting information systems, internal control systems, employee performance